Can I surprise myself? A conceptual framework of surprise self-gifting among consumers. (May 2020) - Gupta, Aditya; Eilert, Meike; Gentry, James W.
Abstract: Consumers frequently purchase self-gifts, i.e. gifts for themselves, for a variety of reasons. Recently, certain items bought as self-gifts have begun to incorporate an element of surprise, as in the case of subscription boxes. Little is known to date, however, about how surprise can influence the self-gifting process. Through a qualitative study, we develop a multi-stage framework illustrating how surprise: (a) transforms the initial stages through heightened anticipation and immersion, and (b) bifurcates the final stage depending on the outcome valence, i.e. positive or negative surprise. Implications for manufacturers and retailers of such products and experiences are then discussed.